FAKTOR INTERNAL BANK TERHADAP PENYALURAN KREDIT - Emanurela Septiatanti W I, 08.05.52.0157; Himmawan, Arief (Students Journal of Accounting and Banking, 2012)
To analyze the effect of the financial ratios of Third Party Funds, Capital Adequacy Ratio, Return on Assets, Non-Performing Loans, and Loan to Deposit Ratio of loans disbursed to the banking company in Indonesia Stock Exchange. The population in this study were used only bank that went public in Indonesia on the Indonesia Stock Exchange, so it is unknown how the influence of the independent variable on the dependent variable in the commercial banks did not go public. Data analysis technique used is multiple linear regression analysis.The results of this study can be concluded that: (1) Third Party Funds variable is positively significant effect on the distribution of credit in the financial statements. (2) Capital Adequacy Ratio variable is significant positive effect on credit disbursement in the financial statements. (3) Return on Assets variable isÂ  positively significant effect on the distribution of credit in the financial statements. (4) variable nonperforming loans have a positive significant effect on the distribution of credit. (5) Loan to Deposit Ratio variables have a positive significant effect on the distribution of credit.Keywords: Third Party Funds, Capital Adequacy Ratio, Return on Assets, Non Performing Loans, and Loan to Deposit Ratio, Loan Disbursement.